Comprehensive genome analyses of Sellimonas intestinalis, a potential biomarker of homeostasis gut recovery. Issue 12 (18th December 2020) - Muñoz, Marina; Guerrero-Araya, Enzo; Cortés-Tapia, Catalina; Plaza-Garrido, Angela; Lawley, Trevor D.; Paredes-Sabja, Daniel
Abstract : Sellimonas intestinalis is a Gram-positive and anaerobic bacterial species previously considered as uncultivable. Although little is known about this Lachnospiraceae family member, its increased abundance has been reported in patients who have recovered from intestinal homeostasis after dysbiosis events. In this context, the aim of the present study was to take advantage of a massive in vitro culture protocol that allowed the recovery of extremely oxygen-sensitive species from faecal samples, which led to isolation of S. intestinalis . Whole genome analyses of 11 S . intestinalis genomes revealed that this species has a highly conserved genome with 99.7 % 16S rRNA gene sequence similarity, average nucleotide polymorphism results >95, and 50.1 % of its coding potential being part of the core genome. Despite this, the variable portion of its genome was informative enough to reveal the existence of three lineages (lineage-I including isolates from Chile and France, lineage-II from South Korea and Finland, and lineage-III from China and one isolate from the USA) and evidence of some recombination signals. The identification of a cluster of orthologous groups revealed a high number of genes involved in metabolism, including amino acid and carbohydrate transport as well as energy production and conversion, which matches with the metabolic profile previously reported for microbiota from healthy individuals. Additionally, virulence factors and antimicrobial resistance genes were found (mainly in lineage-III), which could favour their survival during antibiotic-induced dysbiosis. These findings provide the basis of knowledge about the potential of S. intestinalis as a bioindicator of intestinal homeostasis recovery and contribute to advancing the characterization of gut microbiota members with beneficial potential.